Spike protein of SARS-Cov-2 increases the expression of CXCR4 in breast cancer cells and their migration - Shlapatska, Larysa (PH Akademperiodyka, 2026)
Background and Objectives. There are some data that viral respiratory infections contribute to the metastasis of breast cancer (BC). However, whether the coronavirus SARS-CoV-2 is a trigger for BC progression is not yet clear, as well as the possible mechanisms of its involvement. Aim: to study the effect of the SARS-Cov-2 spike protein (SP) on the expression profile of components of the CXCL12/CXCR4 key signaling аxis of BC, cell adhesion markers CD326, CD54, epithelial cells cytokeratin-18 and β-catenin and migratory activity in in vitro model system. Materials and Methods. The expression profile of the studied markers was detected by flow cytometry after 48 h of incubation of MCF-7 and MDA-MB-231 cell lines with SP. Marker expression was assessed by the number of positive cells (%) and the level of its expression (iMFI). Cell migration was analyzed by the scratch assay after 0, 20 and 28 h for MDA-MB-231 cells and after 0, 24, 48 and 72h for MCF-7 cells of SP treatment. Results. After SP treatment of BC cell lines, a significant increase of CXCR4 expression was detected in cytoplasm of both MCF-7 and MDA-MB-231 cells, and mirror-opposite differences in CXCL12 expression, namely an increase of CXCL12 expression in MDA-MB-231 cells, whereas it was decreased in MCF-7 cells. In addition, in the MCF-7 cell line, after interaction with SP, a decrease in the number of CD54-positive cells, the iMFI of CD326, cytokeratin-18, and a slight increase in the iMFI of β-catenin were detected, while in the MDA-MB-231 cell line, a significant decrease in the iMFI of CD54 was observed. SP accelerates the motility of MDA-MB-231 and MCF-7 cells, which is higher in MDA-MB-231 cells than in MCF-7 cells. Conclusion. The immunophenotypic changes in the expression profile of a number of markers under the influence of SP may indicate the induction of epithelial-mesenchymal transition in MCF-7 cells and increased chemotaxis of MDA-MB-231 cells, however, these conclusions need to be confirmed in functional studies. The fact of increased migration activity of breast cancer cell lines under the influence of SP indicates possible progression of the disease in ВС patients after infection with SARS-CoV-2 or the use of SP-based vaccines, which requires additional research